Nanocrystals of CuMSnS4 (M = In or Ga) for solar energy conversion applications. Issue 83 (2nd October 2018) - Ramasamy, Karthik; Shinde, Pravin S.; Naghibolashrafi, Nariman; Pan, Shanlin; Gupta, Arunava
Abstract : Nanocrystals of wurtzite and defect chalcopyrite phases of CuMSnS4 (M = In or Ga) have been synthesized that exhibit strong visible light absoprtion with a band gap between 1.15 and 1.40 eV. Abstract : Quaternary M I M III M IV XVI4 (I–III–IV–VI4 ) chalcogenides obtained by cross-substitution of binary and ternary compounds remain relatively unexplored. We have for the first-time synthesized wurtzite and defect chalcopyrite phases of CuMSnS4 (M = In or Ga) in the form of nanocrystals. Optical measurements show that the CuMSnS4 (M = In or Ga) nanocrystals exhibit strong visible light absorption with band gap values between 1.15 and 1.4 eV, suitable for solar energy conversion applications.